Effects of resistance exercise on patients with post-stroke dysphagia based on ACSM recommendations: a systematic review of randomized controlled trials - Yu Ye; Kairui Wu; Yingquan Liu; Hongjie Ji; Hongtao Li; Bo Jiang; Fangyuan Xu; Xuejun Li; Peijia Hu; Hongliang Cheng (Frontiers in Physiology)
BackgroundResistance exercise shows potential for improving swallowing function in post-stroke dysphagia (PSD), though optimal dose-response parameters remain unclear. While the American College of Sports Medicine (ACSM) framework effectively guides exercise prescriptions in healthy populations, its application to PSD rehabilitation lacks meta-analytical validation. This study evaluates varying resistance exercise dosages on swallowing outcomes in PSD patients.MethodsWe systematically searched PubMed, Embase, Web of Science, and Cochrane for randomized controlled trials (RCTs) investigating resistance training in PSD. Interventions were stratified using ACSM compliance criteria (6/8 and 7/8 thresholds) into high-adherence versus low/uncertain-adherence groups. Subgroup analyses employed random-effects meta-analyses.ResultsAnalysis included 19 RCTs (n = 566). Using 6/8 ACSM criteria, 11 studies comprised the high-adherence group and eight the low/uncertain group. High-adherence interventions demonstrated improved positively oriented scores [SMD = −1.72 (95% CI −3.26 to −0.18)], enhanced safety [SMD = −0.93 (95% CI −1.54 to −0.32)], and worsened negatively oriented scores [SMD = 2.27 (95% CI 0.66–3.87)]. Low-adherence groups showed non-significant improvements in positively oriented scores [SMD = −0.47 (95% CI −1.02 to 0.09)], negatively oriented scores [SMD = 0.43 (95% CI −0.09–0.94)], and safety [MD = −1.85 (95% CI −3.83 to 0.13)]. Applying stricter 7/8 criteria reclassified nine studies as high-adherence and 10 as low/uncertain. High-adherence groups exhibited greater positively oriented scores improvement [SMD = −2.15 (95% CI −4.11 to −0.20)], safety enhancement [MD = −1.05 (95% CI −1.58 to −0.51)], and negatively oriented scores decline [SMD = 2.85 (95% CI 0.82–4.89)]. Low-adherence groups maintained non-significant outcomes: positively oriented scores [SMD = −0.33 (95% CI −0.75 to 0.10)], negatively oriented scores [SMD = 0.32 (95% CI −0.09–0.74)], and safety [MD = −1.39 (95% CI −2.84 to 0.07)].ConclusionResistance exercise demonstrates superior therapeutic effects over non-resistance interventions for PSD. High adherence to ACSM-recommended dosages yields significantly greater improvements in swallowing function and safety compared to low/uncertain adherence regimens. These findings validate the clinical utility of ACSM guidelines for optimizing resistance exercise prescriptions in PSD rehabilitation.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251041450.